SURGICAL TREATMENT OF CHILDREN WITH CONGENITAL IMPAIRED FORMATION OF VERTEBRAE IN THE LUMBAR SPINE - S. V. Vissarionov (Travmatologiâ i Ortopediâ Rossii, 2012)
A description of the surgical correction technology and the results of surgical treatment of 26 patients with an isolated violation of the vertebrae formation (lateral and posterolateral hemivertebra) at the lumbar spine in Russia and Kazakhstan are presented. The age of patients ranged from 1 year 6 months to 8 years 4 months. After instrumental correction of spinal deformity on the background of the lateral hemivertebrae scoliosis angle ranged from 0 to 6°. The degree of correction ranged from 94 to 100%. After extirpation of the posterolateral hemivertebrae the residual angle of scoliotic deformity ranged from 0 to 4° (average 2,5°), the degree of correction ranged from 95 to 100%, the kyphotic angle of the component from 9 to -6° (average 2,2°). Results were studied in terms from 2 to 7 years after surgery.